Gugurnya Izin Poligami Pengadilan Agama Stabat Perspektif Maqashid Syariah (Telaah Putusan Pengadilan Agama Stabat Nomor 1630/pdt.G/2023/PA.Stb) - Metanur Fazri (Journal Smart Law, 2024)
it is feared that someone will commit an act that violates Islamic law, which of course will violate the maqashid sharia. This study aims to determine the ins and outs of the Religious Court Decision Number 1630/pdt.G/2023/PA.Stb, the basis for decision making and its relationship from the perspective of maqashid sharia. The method in this study is descriptive qualitative with a case approach. The data collection method is by observation, interviews, and documentation. The author conducted data analysis and processing using deductive analysis. The results of the study explain the case of the Religious Court Decision Number 1630/Pdt.G/2023/PA.Stb, which is an application for a polygamy permit submitted by a 33-year-old fish collector who wants to remarry a widow from Malaysia. The applicant has completed the required documents, such as sufficient income and a letter of permission from his first wife, in accordance with applicable legal provisions. The applicant expressed his concern that he would commit acts prohibited by religion because he often went to Malaysia and met his prospective second wife. This is one of the reasons for applying for a polygamy permit. The judge's basis for deciding the Religious Court Decision Number 1630/Pdt.G/2023/PA.Stb which dismissed the polygamy permit application was the consequence of the applicant's absence after the failed mediation process. Although the applicant's substantive reasons for polygamy are acceptable according to law and sharia, negligence of legal procedures is the main reason for the dismissal of this application. This shows the importance of the applicant's consistency and seriousness in following the trial process until completion. The relevance of the religious court decision number 1630/Pdt.G/2023/PA.Stb which dismissed the application for a polygamy permit from the perspective of maqashid sharia is that the decision to dismiss the application for a polygamy permit was based on the absence of the Applicant in the trial process. The judges are of the opinion that maqashid sharia requires cooperation from both parties, but the absence of the applicant hampers the assessment process for this aspect. The dismissal of this application was decided not because of rejection, but due to absence which resulted in the failure to achieve the objectives of maqashid sharia.